VD_FINDINFO Jug / 2020 / 77 vom 20. September 2019 - VD Tribunal cantonal (2019)
CONTRAINTE SEXUELLE, VIOL, LÉSION CORPORELLE SIMPLE, MENACEDROIT PÉNAL, EXPULSIONDROIT PÉNAL | 123 ch. 1 CP, 123 ch. 2 al. 6 CP, 126 al. 1 CP, 126 al. 2 CP, 180 al. 1 CP, 190 al. 1 CP